Aortic valve replacement with combined myocardial revascularisation. Issue 1 (July 1989) - Jones, M; Schofield, P M; Brooks, N H; Dark, J F; Moussalli, H; Deiraniya, A K; Lawson, R A; Rahman, A N
Abstract : Early and late outcome was studied in 630 patients who underwent aortic valve replacement between 1974 and 1982. Group 1 (506 patients) did not have important coronary artery disease, group 2 (69 patients) had coronary artery disease and underwent coronary artery bypass grafting, and group 3 (55 patients) had coronary artery disease but did not undergo myocardial revascularisation. Early mortality (within 30 days of operation) was significantly lower for group 1 (6%) than for group 2 (13%) and for group 3 (16%). Operative mortality in all three groups was lower in patients operated on more recently. The three year survival of patients in group 1 (83%) was significantly higher than that of patients in group 3 (62%) but not than that of patients in group 2 (76%). The findings of this study suggest that the presence of coronary artery disease increases the risk of aortic valve replacement whether or not coronary artery grafting is performed. Myocardial revascularisation, however, seems to return patients with aortic valve and coronary artery disease to a survival curve similar to that of patients with isolated aortic valve disease.